Tradisi Rebu Ngerana Sebagai Bentuk Pantangan Dalam Berbicara Terhadap Pernikahan Adat Karo di Desa Beganding Kecamatan Simpang Empat, Kabupaten Karo - Puja Khairani; Sakti Ritonga; Ismail Ismail (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to provide knowledge about one of the customs and traditions in Beganding Village. The rebu custom is a prohibition on talking between in-laws and sons-in-law and also between in-laws of the opposite sex. The author uses a descriptive method with a type of qualitative research that describes how the practice of banning rebu is carried out and how the Islamic community views the rebu tradition. Data was obtained through observation, interviews and documentation. Next, the presentation and analysis of the data is narrated descriptively. The results of the research show that the Rebu Ngerana tradition is a tradition originating from the Karo community which means taboo/prohibition on speaking. The parties at issue include the man-in-law with the daughter-in-law and the daughter-in-law with the son-in-law and finally the brother-in-law of the opposite sex. There are several forms of rebu in Karo society, namely rebu ngerana or prohibition on talking, prohibition on sitting next to each other between in-laws and daughters-in-law, prohibition on direct eye contact, prohibition on touching body parts, prohibition on one house if there are only parents-in-law and son-in-law in it, prohibition on one field (garden). . based on the informant's explanation that Islam can influence the rebu tradition. Islam teaches kindness and the rebu tradition also teaches good behavior towards in-laws. So both of them teach about things that are good.